Parents and Teachers’ Collaboration on the Performance of Elementary Pupils in the Schools Division of Tarlac Province - Vinson V Pascua; Cristeta C Dulos (ASEAN Journal of Basic and Higher Education, 2020)
This study determined the frequency of the collaboration of teachers and parents in school-based activities and home-based activities and the performance of the elementary pupils in the Schools Division of Tarlac Province. It utilized a descriptive correlational design. In gathering the data, a researcher – made questionnaire was given to the respondents. Descriptive statistics and multivariate analysis of variance were used to treat the data gathered. The findings indicated that the parents are predominantly female, they are in the middle stage of adulthood, married, most of them are housewives, and they are secondary graduate. Moreover, the teachers are mostly female, they are middle aged, married, majority of them have master’s unit, and they are in the teaching profession for about eleven to twenty years. Furthermore, results disclosed no significant difference in the frequency of Collaboration between Teachers and Parents. Seemingly, a highly significant relationship was distinguished between the frequency of collaboration of parents and teachers and the level of pupil’s performance. Based on the results, the researcher recommends management of time in school for the teachers to produce more educational materials that can help the parents in remediating their children; meetings between parents and teachers for them to tackle the improvement of the pupils; inclusion of home visitation in classroom program; continuous engagement in prioritizing seminars that can improve pupil’s behavior; strengthening of collaboration by ensuring the school as a welcoming place for the parents; and utilization of gadgets as a means of communication between parents and teachers so that the collaboration will be nourished.